A Deterministic Approach for Designing Flat Gain Ultra-Wideband LNAs - Belen, Mehmet Ali; Gunes, Filiz; Demirel, Salih; Mahouti, Peyman (IEEE, 2014)
In this paper, a deterministic approach is presented for designing flat gain, ultra-wideband single - stage Low Noise Amplifier LNAs. The approach is based upon the solutions of the nonlinear noise F, input VSWR V-in and gain G(T) equations of the employed microwave transistor with respect to its stable source Z(S) and load Z(L) terminations for the performance (F(f)>= F-min(f), V-in(f) >= 1, G(Tmin)(f)<= G(T)(f)<= G(Tmax)(f)) triplets, where F-min(f) and G(Tmax) ,((min))(f) are the achievable minimum noise and maximum (minimum) gain at f of the bias condition V-DS, I-DS respectively. A Performance Data Bank PDB is constructed by the compatible performance triplets so that it can be conveniently used to design any LNA with the required gain, noise and input VSWR characteristics along the available operation bandwidth of the device. Even the bias condition (V-DS, I-DS) can be selected subject to the sensitivity requirements by adding a black-box artificial model of the transistor in front of the PDB. In this work, finally we present the two flat gain ultra-wideband LNA design alternatives with respect to the tolerance and bandwidth choices using the microwave transistor NE3509M04 together with their (Z(S), Z(L)) termination couples.
Keywords: Linear Amplifier; Noise Figure; Input VSWR; Transducer Gain; Computer Science; Physics; Telecommunications